Effect of Bacterial Vaginosis (BV)-HIV-1 Co-existence on Maternal and Infant Health: A Secondary Data Analysis - Mwenda, Ngugi; Nduati, Ruth; Kosgey, Mathew; Kerich, Gregory (Frontiers in Pediatrics, 2021)
Background: The lactobacillus-rich microbiome forms a defense system against infections. Babies are born sterile and acquire their microbiome from exposure to the mothers' vaginal and rectal microbiota. Bacterial vaginosis (BV), which is characterized by a deficit of the Lactobacilli genera, may predispose women and their babies to an increased frequency of illness. Objective: To determine the effect of BV on HIV-infected women's post-delivery health as well as the morbidity and mortality of the exposed infant at birth, 6 months, and at 12 months of life. Study Design: A retrospective cohort study was conducted using previously collected data to investigate whether there was an association between BV-HIV-1 infected mothers and subsequent infant morbidity and mortality over a 12-month period. Methods: Data for this analysis were extracted from the original data set. Women were categorized into two groups according to whether they had a positive or negative laboratory-based diagnosis of BV using the Nugent method. The two groups were compared for socio-demographic characteristics, prior to the pregnancy experience in their current pregnancy outcome and at post-delivery morbidity, and for the duration of hospital stay. BV-exposed and unexposed infants were compared in terms of morbidity and mortality at birth, and in the periods between birth and 6 months, and between 6 and 12 months, respectively, based on prospectively collected data of the mother's past and present illness, and clinical examination at scheduled and unscheduled visits during the follow-up period of the original study. The generalized estimating equation (GEE) was used to analyze the longitudinally collected data. We used the Kaplan-Meier (KM) method to generate the cumulative hazard curve and compared the mortality in the first year of life between the two groups. Results: In total, 365 patients were included in the study. Exposure to BV was associated with an adverse maternal condition (Relative Risk [RR], 2.45; 95% confidence interval [CI], 1.04–5.81, P = 0.04) and maternal hospital admission (RR, 1.99; 95% CI, 1.14–3.48, P = 0.02) but was not linked to any neonatal morbidity at birth. There was a higher frequency of gastro-intestinal morbidity among BV-exposed infants. At 6 months, infants of BV-exposed mothers had higher odds of bloody stool (Odds Ratio [OR], 3.08; 95% CI, 1.11–10.00, P = 0.04), dehydration (OR, 2.94; 95% CI, 1.44–6.37, P = 0.01), vomiting (OR, 1.64; 95% CI, 1.06–2.56, P = 0.03), and mouth ulcers (OR, 12.8; 95% CI, 2.27–241.21, P = 0.02). At 12 months, exposure to BV was associated with dehydration (OR, 1.81; 95% CI, 1.05–3.19, P = 0.03) and vomiting (OR, 1.39; 95% CI, 1.01–1.92, P = 0.04). KM survival analysis showed non-significant higher trends of deaths among BV-exposed infants (P = 0.65). Conclusion: This study demonstrates differences in maternal and infant morbidity outcomes associated with exposure to BV. Further research is required to determine whether treatment for maternal BV mitigates maternal and infant morbidity.